PERAN ROOMBOY DI MUTIARA MERDEKA HOTEL PEKANBARU - Putri Nilam Sari; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Hospitality is part of the tourism industry that sells accommodation services in which there are elements of service, comfort, and lodging facilities needed for those who need lodging facilities for family or holiday purposes. A hotel must provide the best product quality and service quality, because a hotel must provide the best impression and experience for guests during their stay. This is why housekeeping in hotels is very important. The purpose of this study was to identify and analyze the role of roomboys and roomboy constraints in providing room servic eat Mutiara Merdeka Hotel Pekanbaru. In this study the authors used qualitative research methods. The results of this study indicate that the role of roomboys at Mutiara Merdeka Hotel Pekanbaru is managing rooms, serving guests, carrying out orders from superiorss, cooperating with fellow roomboys, cooperating with the housekeeping department and cooperating with other departments such as the front office and food and beverage service as well as several constraints experienced by roomboy in serving guests Keywords: Role, Roomboy, Hotel